Safety and Efficacy of Apatinib Monotherapy for Unresectable, Metastatic Esophageal Cancer: A Single‐Arm, Open‐Label, Phase II Study. (29th May 2020) - Yanwei, Li; Feng, He; Ren, Peng; Yue, Jie; Zhang, Wencheng; Tang, Peng; Shang, Xiaobin; Pang, Qingsong; Liu, Dongying; Chen, Chuangui; Pan, Zhanyu; Tao, Yu Zhen
Abstract: Lessons Learned : Patient compliance with the oral dosage treatment was good, with no need for hospitalization. Patients with tracheal and esophageal fistulas can take crushed apatinib by nutrient tube, with the same bioavailability and efficacy. Apatinib may be an effective and safe second‐ or further‐line treatment for advanced esophageal cancer. Background: Apatinib is an inhibitor of vascular endothelial growth factor receptor‐2 (VEGFR2), which is thought to play a role in esophageal cancer progression. Our goal was to evaluate the efficacy and safety of apatinib in patients with unresectable esophageal cancer and to examine whether VEGFR2 expression influenced the clinical response. Methods: This single‐arm, open‐label, investigator‐initiated phase II study enrolled patients with advanced squamous cell carcinoma (SCC) or adenocarcinoma of the esophagus or esophagogastric junction who were admitted to Tianjin Medical University Cancer Institute and Hospital between August 2017 and January 2019. Apatinib monotherapy (500 mg/day) was given orally or via an enteral tube until disease progression, unacceptable toxicity, withdrawal, or death. Patients were followed until treatment was discontinued or death. The main endpoints were tumor response, progression‐free survival (PFS), overall survival (OS), and adverse events (AEs). Results: Among 32 patients screened for inclusion, 30 were included in the safety and survival analyses (i.e., received apatinib), and 26 were included in the efficacy analysis (at least one imaging follow‐up). Median follow‐up time and exposure to apatinib were 5.34 months and 72 days, respectively. Among 26 patients included in the efficacy analysis, 2 had a partial response (PR; 7.7%) and 14 had stable disease (SD; 53.8%). The overall response rate (ORR) was 7.7%, and the disease control rate (DCR) was 61.5%. Median PFS and OS were 4.63 months (95% confidence interval, 2.11–7.16 months) and 6.57 months (4.90 months to not estimable), respectively. Fifteen patients (50.0%) experienced treatment‐related AEs, most commonly hypertension (26.7%), diarrhea (20.0%), and hand‐foot‐skin reaction (10.0%). No patients had grade ≥4 treatment‐related AEs. Conclusion: Apatinib was effective as second‐ or further‐line treatment for advanced esophageal cancer.